Management : - Kinicki, Angelo. (McGraw-Hill/Irwin, 2008)
Blending scholarship and imaginative writing, ASU business professor Kinicki (of Kreitner/Kinicki Organizational Behavior 7e) and writer Williams (of Williams/Sawyer Using Information Technology 7e) have created a highly readable introductory management text with a truly unique student-centered layout certain to be well received by today's visually oriented students. The authors present all basic management concepts and principles in "bite-size" chunks, 2- to 6-page sections to optimize student learning. The text emphasizes practicality of information presented and supports both the instructor and the students with a wealth of classroom-tested resources.